Peningkatan hasil belajar pada pembelajaran tematik melalui contextual teaching and learning berbantu media powerpoint pada siswa kelas II SD Negeri 3 Bojong Kabupaten Purbalingga tahun pelajaran 2020/2021 - Hikmah Nurchasanah (Jurnal Kualita Pendidikan, 2020)
The purpose of this study was to determine the improvement of learning outcomes in thematic learning through the application of the Contextual Teaching and Learning Model assisted by Powerpoint media. The subjects in this study were 28 children. The data collected in this study is data about the ability to solve thematic problems with the Contextual Teaching and Learning Model assisted by Powerpoint media. The results of this study indicate that the application of the Contextual Teaching and Learning Model assisted by Powerpoint media can improve learning outcomes, namely from cycle I to cycle II by 28% from moderate to high criteria. The results showed that the Contextual Teaching and Learning Model assisted by Powerpoint media can improve learning outcomes in thematic learning.